PERILAKU MASYARAKAT TERHADAP EFISIENSI PEMANFAATAN AIR BERSIH RUMAH TANGGA DI KOTA BANDA ACEH - Ahmed Siddiq Hawari; Nur Aidar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
AbstractThis study aims to determine the efficiency of water use in Banda Aceh City. Primary data was used in this study with a sample of 100 respondents. Data were analyzed using DEA. The results showed that the range of efficiency in water use was found to be at most in the range of 75-100 percent, with a sample of 55 respondents, meaning that 50 percent of the respondents interviewed were efficient in using water in their respective households, especially for households type 36 and type 45. The suggestion that can be conveyed is that there is a need for an appeal and socialization from the government for the community to make a movement to save water use so that water does not become scarce.Keywords: Water use, Efficiency, DEA